2019
DOI: 10.1039/c9qi00040b
|View full text |Cite
|
Sign up to set email alerts
|

Copper-containing hybrid compounds based on extremely rare [V2Mo6O26]6– POM as water oxidation catalysts

Abstract: Hybrid Cu/V/Mo compounds with rare [α-V2Mo6O26]6– and oxides prepared by their thermal degradation were used as catalysts for water oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…[148][149][150][151] However, more recent studies confirmed the molecular integrity of many molecular WOCs. Particularly, studies on the structural integrity of Cu-containing [V 2 Mo 6 O 26 ] 6À POM-WOCs 152 showed that these POMs do not exhibit nanoparticle growth (0.04 M borate buffer, pH 8) based on DLS experiments. Regarding the Cu-sites, their high activity and low overpotential are controlled by their coordination environment.…”
Section: Chem Soc Rev Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…[148][149][150][151] However, more recent studies confirmed the molecular integrity of many molecular WOCs. Particularly, studies on the structural integrity of Cu-containing [V 2 Mo 6 O 26 ] 6À POM-WOCs 152 showed that these POMs do not exhibit nanoparticle growth (0.04 M borate buffer, pH 8) based on DLS experiments. Regarding the Cu-sites, their high activity and low overpotential are controlled by their coordination environment.…”
Section: Chem Soc Rev Review Articlementioning
confidence: 99%
“…The first oneelectron oxidation leads to the formation of Cu III -OH species followed by Cu IV QO oxidation, which assists in nucleophilic attack, while the aqua-oxo interaction favour the formation of intramolecular O-O bonds. 152 Other works on the molecular 4 ] in alkaline solution 131 indicated that the structure of the Cu 4 O 4 core remains intact, with no oxide formation during the OER. The two-electron transfer processes involved in the tetranuclear Cu 4 O 4 -cubane centers yield high-valent Cu III /Cu III O intermediates during the OER (Fig.…”
Section: Chem Soc Rev Review Articlementioning
confidence: 99%
“…[2] Nevertheless, more recently, we can find examples of similar polyanionic nanostructures containing elements for the f, [3][4][5][6] and p groups. [7,8] During the last years, the applications of this family of compounds have been explored intensively and found their way in various fields such as the decontamination of water, [9] flash memory devices, [10] qubits, [11] water splitting [12] as well as in biomedical research exploring their function as antiviral or antitumoral drugs. [13][14][15] However, biomedical studies were still scarce in the latter case in the 90s as discussed in the review of Rhule et al [13] It was during the early-mid 2000s when systematic studies on the application of POMs to cancer treatment increased exponentially.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] This paper is a continuation of our research devoted for the synthesis of hybrid compounds based on POMs under mild conditions. 3,4,[28][29][30] Our work is focused on the study of inuence of synthetic conditions such as the stoichiometry of reagent, metal sources in the reaction mixtures and the time of interaction. Previously…”
Section: Introductionmentioning
confidence: 99%